2009
DOI: 10.1111/j.1365-246x.2008.04068.x
|View full text |Cite
|
Sign up to set email alerts
|

Energy partition of seismic coda waves in layered media: theory and application to Pinyon Flats Observatory

Abstract: International audienceWe have studied the partition of shear, compressional and kinetic energies in the coda of ten earthquakes recorded on a dense array, located at Pinyon Flats Observatory (PFO), California. We observe a clear stabilization of the shear to compressional ($W^s/W^p$) energy ratio in the coda, with an average value of about 2.8. The ratio between the vertical and horizontal kinetic energies ($V^2/H^2$) can be measured from 5 to 25Hz and shows an abrupt transitionfrom 0.1 in the 5-10Hz band, to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 34 publications
3
75
0
Order By: Relevance
“…Furthermore, the duration to reach the same decay rate seems to become longer as hypocentral distance increases. Although the energies of P and S modes and those of vertical and horizontal components obviously have different physical meanings [e.g., Margerin et al, 2009], the observed same decay rate at short lapse time and the dependence of the duration on hypocentral distance are qualitatively consistent with the establishment of equipartition shown in Figure 7a.…”
Section: Energy Partitioningsupporting
confidence: 71%
“…Furthermore, the duration to reach the same decay rate seems to become longer as hypocentral distance increases. Although the energies of P and S modes and those of vertical and horizontal components obviously have different physical meanings [e.g., Margerin et al, 2009], the observed same decay rate at short lapse time and the dependence of the duration on hypocentral distance are qualitatively consistent with the establishment of equipartition shown in Figure 7a.…”
Section: Energy Partitioningsupporting
confidence: 71%
“…In the auto-correlation approach, we can determine the velocity structure immediately below the observed site because of the direct correspondence of the imaginary part of the Green's function to the spectral energy density . As a pioneering work, Margerin et al (2009) showed that after sufficient lapse time from the onset of the S-wave the late coda can be considered to be in the diffuse field regime. Then, Kawase et al (2011) extended the idea of DFC to the stack of horizontal-to-vertical ratios of earthquakes (EHVR) and provided a simple theoretical formula assuming equipartition of energy in the incident waves at the bedrock (i.e., equipartition inside the half-space).…”
Section: Introductionmentioning
confidence: 99%
“…The partitioning between P and S energy is one observable that is difficult to measure (Shapiro et al 2000;Hennino et al 2001;Margerin et al 2009) in the field but can easily be simulated . According to Ryzhik et al (1996) the theoretical value for the S-to P-energy ratio for long lapse times tends to stabilize in infinite space at…”
Section: Discussionmentioning
confidence: 99%